Application of GIS Techniques to Determine Suitable Areas for Artificial Groundwater Recharge in Kollimalai Hills - Subramani, T; Rokith, K (International Journal of Engineering and Technology, 2018)
The groundwater is taken into consideration because the foremost source of ninety nine % of all retrievable clean water, optimization of its utilization could be very essential. Identity of potential zones for groundwater recharge has end up an essential occasion to fill up the groundwater sources. The recharge ability is ruled by various functions of surface, subsurface and hydro meteorological parameters. Remote sensing approach is observed to be very powerful device for the combination of various functions of these elements. In this work, an try has been made to identify groundwater recharge potential zones in Kollimalai hill. Namakkal district which is located in Â Tamilnadu , India. Evaluation (WIOA) changed into done in this study using the software Arc GIS by using integrating the thematic layers of geology, soil, geomorphology, land use/ land cowl geology, geomorphology, lineament, land use/ land cowl, groundwater degree and slope, rainfall. The groundwater potentials were described as suitable, moderately suitable and unsuitable. Â Â Â